The German 3G Licence Auction: Did the Government's Stake in Deutsche Telekom Influence the Outcome? - Robin Rander (Lund University, School of Economics and Management, Department of Economics, 2004)
The spectrum for third generation (3G) mobile communications for the German market was alloted to operators by means of an auction. This resulted in a highly competitive outcome: six operators were given rights to provide 3G services. Government revenues from this auction were a staggering EUR 50.8 Bn. As the German government stands as majority shareholder in one of the strongest participants, Deutsche Telekom (DT), it was argued that DT had an incentive to push prices to higher levels than had otherwise been motivated, thereby servicing the interest of the majority shareholder. This paper provides a theoretical model which shows that the German auction rules were indeed vulnerable to such a conflict of interests. However, the only equilibrium of the model consistent with observed behaviour corresponds to a conflict of interest (in the context of the model) too small to have any impact on the behaviour of DT.
Keywords: D43; D44; D45; H82; L13; 330; Auction theory; Telecommunications; Game theory; Toe hold